Macromammal and bird assemblages across the late Middle to Upper Palaeolithic transition in Italy: an extended zooarchaeological review. (20th June 2020) - Romandini, Matteo; Crezzini, Jacopo; Bortolini, Eugenio; Boscato, Paolo; Boschin, Francesco; Carrera, Lisa; Nannini, Nicola; Tagliacozzo, Antonio; Terlato, Gabriele; Arrighi, Simona; Badino, Federica; Figus, Carla; et al.
Abstract: Evidence of human activities during the Middle to Upper Palaeolithic transition is well represented from rock-shelters, caves and open-air sites across Italy. Over the past decade, both the revision of taphonomic processes affecting archaeological faunal assemblages and new zooarchaeological studies have allowed archaeologists to better understand subsistence strategies and cultural behaviors attributed to groups of Neandertal and modern humans living in the region. This work presents the preliminary results of a 5-years research programme (ERC n. 724046 – SUCCESS) and offers a state-of-the-art synthesis of archaeological faunal assemblages including mammals and birds uncovered in Italy between 50 and 35 ky ago. The present data were recovered in primary Late Mousterian, Uluzzian, and Protoaurignacian stratigraphic contexts from Northern Italy (Grotta di Fumane, Riparo del Broion, Grotta Maggiore di San Bernardino, Grotta del Rio Secco, Riparo Bombrini), and Southern Italy (Grotta di Castelcivita, Grotta della Cala, Grotta del Cavallo, and Riparo l'Oscurusciuto). The available Number of Identified Specimens (NISP) is analysed through intra- and inter-site comparisons at a regional scale, while aoristic analysis is applied to the sequence documented at Grotta di Fumane. Results of qualitative comparisons suggest an increase in the number of hunted taxa since the end of the Middle Palaeolithic, and a marked change in ecological settings beginning with the Protoaurignacian, with a shift to lower temperatures and humidity. The distribution of carnivore remains and taphonomic analyses hint at a possible change in faunal exploitation and butchering processing between the Middle and Upper Palaeolithic. A preliminary comparison between bone frequencies and the distribution of burned bones poses interesting questions concerning the management of fire. Eventually, the combined use of relative taxonomic abundance and aoristic analysis explicitly addresses time averaging and temporal uncertainty embedded in NISP counts and offers estimates of absolute change over time that can be used to support hypotheses emerging from taxon relative frequencies.